Current Strategies of Scientific and Methodological Support of Teachers as a Mechanism for the Formation of a Unified Educational Space - I.V. Golovina; G.A. Paputkova; T.Y. Medvedeva; V.V. Rubtsov; O.V. Vikhristyuk; O.I. Leonova (Психологическая наука и образование)
This publication examines the features of the integration of universities into the system of scientific and methodological support for teaching and HR staff. The most significant areas of activity of scientific and methodological centers for supporting teaching staff, created on the basis of universities, are analyzed to improve the conditions for improving the professional skills of teaching and HR staff. The central issue of discussion is the definition of strategies for the activities of scientific and methodological centers oriented on solving problems within the framework of the formation of a unified educational space in the Russian Federation. Strategies for scientific and methodological support of teaching staff are considered based on the practical experience of universities in implementing educational and scientific projects in accordance with the criteria, which determines the increase of the innovative potential in organizations, the practical significance of the content and forms of scientific and methodological support, the formation of infrastructure for supporting teaching staff, problem specialization and expertise in the activities of scientific and methodological centers, as well as the development of the interaction with professional communities.